Increased detection of Plasmodium knowlesi in Sandakan division, Sabah as revealed by PlasmoNex™ - Goh, Xiang Tong; Lim, Yvonne Ai Lian; Indra Vythilingam; Chew, Ching Hoong; Lee, Ping Chin; Ngui, Romano; Tan, Tian Chye; Yap, Nan Jiun; Veeranoot Nissapatorn; Chua, Kek Heng (BioMed Central Ltd., 2013)
Background Plasmodium knowlesi is a simian malaria parasite that is widespread in humans in Malaysian Borneo. However, little is known about the incidence and distribution of this parasite in the Sandakan division, Malaysian Borneo. Therefore, the aim of the present epidemiological study was to investigate the incidence and distribution of P. knowlesi as well as other Plasmodium species in this division based on a most recent developed hexaplex PCR system (PlasmoNex™).